PENGARUH KONDISI EKONOMI ORANG TUA TERHADAP MOTIVASI BELAJAR SANTRI KELAS XI MA TAHUN AJARAN 2020-2021 DI PONDOK PESANTREN MODREN DINIYYAH PASIA - Gita Rizkia (El-Rusyd, 2021)
The economic situation of parents is closely related to the learning motivation of children at school, students who have different economies from one another. Different economies, the motivation to learn will also be different and varied. The purpose of this study is to describe the economic situation of the families of the Islamic boarding school students in the modern diniyyah Islamic boarding school, to find out about how the learning motivation of the students at the modern diniyyah Islamic boarding school, and to determine the effect of the economic situation and the motivation of the students on the learning achievement of the students at the modern diniyyah Islamic boarding school. the population in this study were students of class XI MA in the academic year 2020-2021 as many as 110 people, and the sample in this study was 30 people from the population above. Data collection techniques in this study the authors used several methods, namely: questionnaires and questionnaires. , documentation, validity test and reliability test.This type of research is quantitative research with the type of expost facto research. Based on the level of explanation, this research includes causal associative research, because this research aims to identify the effect of elastic X on Y which is causal in nature. This type of research is to examine the influence of parents' economic conditions (X) on learning motivation in class XI MA students for the 2020-2021 academic year at the Modren Diniyyah Pasia Islamic Boarding School (Y). The data was obtained from a questionnaire given to 30 respondents who examined property ownership, type of parental education, family income, family expenses and type of residence. Analysis of the data used in this study is multiple regression analysis using the SPSS IBM Statistics 25 For Windows program.The result of this research is significant by calculating the correlation, so it can be seen that rcount is greater than rtable (rcount > rtable) with an error rate of 5% (0.729 > 0.361). There is a significant influence between the economic conditions of parents on the learning motivation of class XI MA students for the 2020-2021 academic year at the Modren Diniyyah Pasia Islamic Boarding School. Furthermore, the correlation coefficient of 0.729 which can be high/strong correlation with the interpretation of r = 0.70 to 0.90 (between variable X and variable Y there is a high/strong relationship).